Legal gender recognition in Portugal: a path to self-determination - Moleiro, C. (2021)
This paper presents research onthe enforcement and impact of the first legal gender recognition legislation in Portugal (Law no.7/2011). The study describes how the administrative process created by the law functioned during its initial 5-year period, and identifies challenges and processes of resistance to this legal innovation.Simultaneously, it seeks to assess the impact of the law on the social and psychological well-being of trans people, including in their access to vital spheres of social life such as education and employment. The research employs a mixed-methods approach and a multi-informant methodology: an online questionnaire was completed by 68 trans and non-binary people, and semi-structured in-depth interviews were carried out with various selected stakeholders: representatives of trans and LGBTIQ+ organisations (n=5), health professionals identified as experts in the topic and as gatekeepers in legal gender recognition processes (n=12), and trans people (n=6). Results show, on the one hand, the significant positive impact that legal gender recognition has on the psychological well-being and social welfare of the participants. On the other hand, results also show several challenges and forms of resistance to the implementation of the law, in particular those challenges resulting from the fact that legal gender recognition depended on a clinical diagnosis and the provision of a clinical report.